2018
DOI: 10.1371/journal.pntd.0006604
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological factors and risk of hemorrhagic fever with renal syndrome in Guangzhou, southern China, 2006–2015

Abstract: BackgroundThe epidemic tendency of hemorrhagic fever with renal syndrome (HFRS) is on the rise in recent years in Guangzhou. This study aimed to explore the associations between meteorological factors and HFRS epidemic risk in Guangzhou for the period from 2006–2015.MethodsWe obtained data of HFRS cases in Guangzhou from the National Notifiable Disease Report System (NNDRS) during the period of 2006–2015. Meteorological data were obtained from the Guangzhou Meteorological Bureau. A negative binomial multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
4
31
2
Order By: Relevance
“…Temperature is another important driver (IRR = 1.195, 95% CI 1.024-1.395) for the pertussis infection in this work. Temperature has been shown to be in relation to many contagious diseases, such as scarlet fever 65 , HFRS 20 , bacillary dysentery 21 , and human brucellosis 22 . Similarly, in the present work, we found that the monthly average temperature is positively correlated with the number of pertussis cases, which can also be used to explain the peak phenomenon of pertussis incidence observed in hot weather in our study and previous other studies 53,66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is another important driver (IRR = 1.195, 95% CI 1.024-1.395) for the pertussis infection in this work. Temperature has been shown to be in relation to many contagious diseases, such as scarlet fever 65 , HFRS 20 , bacillary dysentery 21 , and human brucellosis 22 . Similarly, in the present work, we found that the monthly average temperature is positively correlated with the number of pertussis cases, which can also be used to explain the peak phenomenon of pertussis incidence observed in hot weather in our study and previous other studies 53,66 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the relationship between weather variability and contagious diseases has received increasingly wide attention, because climatic drivers may play a pivotal role in the dynamics, distribution, and transmission of contagious diseases via impacting the growth and development of pathogenic agents, population dynamics of hosts and human behaviors, and thus can be deemed as early warning signals for the dynamic epidemics of contagious diseases 15,16 . Presently, many publications have found that meteorological parameters are closely related to the incidences of scarlet fever 17 , tuberculosis 18 , dengue fever 19 , hemorrhagic fever with renal syndrome (HFRS) 20 , bacillary dysentery 21 , human brucellosis 22 , hand, foot and mouth disease (HFMD) 23 , etc. Prior studies also reported the relationship between weather parameters and pertussis.…”
mentioning
confidence: 99%
“…Previous studies focused on large scale evaluations of HFRS epidemiology, especially country and city level, [3][4][5][6][7][8] and these studies gave a global description of HFRS transmission in China. Given that small-scale studies will yield more precise and a better quantification of the local characteristics of HFRS transmission, the present study chose four high-risk HFRSaffected counties from Heilongjiang and Shaanxi provinces, where the largest number of HFRS cases are documented in China.…”
Section: Introductionmentioning
confidence: 99%
“…1). The causes for the summer peak and the variation of the number of cases in different years may be explained by the warm temperature, high humidity and high precipitation in the sub-tropical Lingnan region, where Guangzhou is located (19).…”
Section: Discussionmentioning
confidence: 99%